FORMATION OF PRIORITY DIRECTIONS OF THE STATE REGULATION OF DEMOGRAPHIC PROCESSES IN UKRAINE - Dolinchenko O.М. (Pressing Problems of Public Administration, 2017)
The article studies the opportunities of demographic development caused by the need to mitigateeffects of the demographic crisis, to eliminate threats in the social and economic sphere in general, toovercome the demographic crisis and to achieve sustainable demographic development, normalizationof reproduction of the population is a long and complex process.